EVALUASI PERESEPAN OBAT BERDASARKAN INDIKATOR WORLD HEALTH ORGANIZATION (WHO) DI PUSKESMAS TELING ATAS - meliska debora saibaka; Widya Lolo; Karlah Mansauda (UNIVERSITAS SAM RATULANGI, 2022)
ABSTRACTIrrational prescription can cause polypharmacy, resistance, and medication interactions, thus, evaluation of prescription medication should be compulsory. This study aimed to determine the appropriate percentage of prescription medication at Community Health Centre in Teling Atas in comparison with prescription indicators of WHO. Data gathering methods was carried out using random sampling. The study finding indicated that the average of medication in each prescription is 2.49, prescription with generic names is 97.06%, antibiotic prescription is 24.80%, the use of injection preparation is 0%, and the item percentage of drugs prescribed according to National Formulary is 81.97%. Based on the finding acquired, it was concluded that the percentage of prescription with generic names and the percentage of injection preparation are consistent, however, the item average of drugs in each prescription, the percentage of antibiotic prescription, and the percentage of national formulary drugs are not. Keywords: Prescription, WHO Indicator, Community Health Centre. ABSTRAKPeresepan yang tidak rasional dapat menyebabkan polifarmasi, resistensi dan terjadinya interaksi obat, untuk itu diperlukan evaluasi peresepan obat. Penelitian ini bertujuan untuk mengetahui persentase kesesuaian peresepan obat di Puskesmas Teling Atas dibandingkan dengan indikator peresepan WHO. Metode pengumpulan data dilakukan dengan random sampling. Hasil yang diperoleh yaitu rata-rata item obat tiap lembar resep sebesar 2,49 rata-rata item, peresepan dengan nama generik 97,06%, peresepan antibiotik 24,80%, penggunaan sediaan injeksi sebesar 0% dan persentase item obat yang diresepkan sesuai dengan Formularium Nasional 81,97%. Berdasarkan hasil yang diperoleh dapat disimpulkan bahwa persentase peresepan dengan nama generik dan persetase peresepan sediaan injeksi sudah sesuai sedangkan rata-rata item obat tiap lembar resep, persentase peresepan obat antibiotik dan persentase item obat formularium nasional tidak sesuai. Kata Kunci: Resep, Indikator WHO, Puskesmas.